No QTc prolongation with CDK 4/6 inhibitor FCN-437c: results of a concentration-QTc analysis from a dedicated study in adult healthy subjects - Zhao, Lin; Sun, Yi; Yang, Xiaoran; Tian, Ling; Li, Lize; Wang, Fangfang; Niu, Xiaoye; Diao, Lei; Li, Haiyan (Frontiers in Pharmacology, 2024)
Cardiotoxicity and QT interval prolongation have been a common cause of withdrawal of drugs from the market. FCN-437c is an oral, second-generation, potent, and selective CDK4/6 inhibitor for the treatment of patients with HR+/HER2-metastatic breast cancer. A single-center, double-blind, randomized, and placebo-controlled clinical study in healthy subjects was conducted to investigate the QTc prolongation potential of FCN-437c utilizing Concentration-QTc (C-QTc) modeling approach. FCN-437c was administered at doses of 300, and 400 mg with single oral administration, along with placebo, in 18 healthy subjects. Electrocardiograms (ECGs) through 24 hour holter monitor and blood samples were collected. The Cmax of 400 mg single dose in healthy subjects is similar to that from therapeutic dose 200 mg QD at steady state in patients with cancer. The 90% CI upper limit of ΔΔQTcF at the Cmax geometric mean in both dose groups were < 10 ms. It is concluded that FCN-437c has low risk of prolonging the QT interval at therapeutic dose.